Marine wind power cable industrial wire and its production process

CN122879849APending Publication Date: 2026-10-09HANGZHOU DIKAI IND FABRICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611150654.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0004]针对现有技术中存在的不足,本发明提供了一种海洋风力发电用缆绳工业丝及其生产工艺,以解决现有缆绳用纤维耐老化性能差、耐磨性能不足、海水浸泡后强度衰减快、不具备微损伤自修复等问题

Benefits of technology

[0042]高粘锦纶6切片作为成纤基体树脂,为工业丝提供基础力学支撑;一体化功能母粒实现多种功能组分的均匀分散与协同增效,改善工业丝的综合性能;紫外线吸收剂可抑制紫外线对工业丝的降解作用,提升工业丝的耐光性能;分散剂可促进各原料组分在制备过程中的分散均匀,减少组分团聚现象;疏水耐磨自修复涂层组合物可在工业丝表面形成连续致密的防护涂层,提升工业丝的疏水性能、耐磨性能及损伤修复能力,各组分协同作用,使所得工业丝能够适配海洋风力发电系泊缆绳的严苛服役环境。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application provides a marine wind power cable industrial yarn and a production process thereof, and the preparation raw materials of the marine wind power cable industrial yarn include, in terms of weight parts, 80-95 parts of high-viscosity polyamide 6 chips, 6-12 parts of an integrated functional master batch, 0.3-0.6 parts of an ultraviolet absorber, 0.2-0.5 parts of a dispersing agent and 4-8 parts of a hydrophobic wear-resistant self-repairing coating composition (calculated in terms of solid content). The cable industrial yarn provided by the application has excellent mechanical properties, light resistance, hydrophobic wear resistance and other comprehensive properties, and can meet the harsh working condition requirements of the marine wind power mooring cable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of industrial synthetic fiber filament technology, specifically to an industrial filament for marine wind power generation cables and its production process. Background Technology

[0002] As global offshore wind power development continues to expand into deep-sea areas, mooring cables, as key anchoring components of offshore wind power platforms, are subjected to multiple extreme and harsh conditions, including high salt spray, strong ultraviolet radiation, high-frequency wave impact, continuous seawater immersion, and microbial adhesion. This places demands on the comprehensive performance of the fiber materials used, far exceeding those of conventional industrial fibers. Traditional polyester fibers have a high tensile modulus and low elongation at break, making it difficult to effectively absorb the dynamic impact loads from waves and unsuitable for the flexible buffering requirements of deep-sea mooring. While conventional nylon 6 industrial yarn possesses good toughness and elasticity, meeting basic mechanical and deformation adaptation requirements, it suffers from poor resistance to light aging, insufficient surface abrasion resistance, significant strength degradation after seawater immersion, and lacks the ability to self-repair micro-damage under long-term marine service conditions. It is difficult to simultaneously achieve a synergistic balance between high strength, high abrasion resistance, seawater corrosion resistance, and long-term weather resistance, thus failing to meet the long-term service requirements of deep-sea wind power mooring cables.

[0003] Currently, fiber materials used in offshore wind power mooring cables generally suffer from problems such as insufficient mechanical load-bearing capacity of the matrix resin, uneven dispersion and easy agglomeration of functional components, poor resistance to photo-oxidative aging, and lack of a protective layer on the fiber surface that combines hydrophobicity, wear resistance, and micro-damage self-repair function, making it difficult to meet the harsh operating conditions of offshore wind power mooring cables. Summary of the Invention

[0004] To address the shortcomings of existing technologies, this invention provides an industrial fiber for marine wind power cable and its manufacturing process, which solves problems such as poor aging resistance, insufficient abrasion resistance, rapid strength decay after seawater immersion, and lack of micro-damage self-repair in existing cable fibers.

[0005] To achieve the above objectives, the present invention provides the following technical solution:

[0006] This invention provides an industrial yarn for marine wind power generation cables. By weight, the raw materials for its preparation include: 80-95 parts of high-viscosity nylon 6 chips, 6-12 parts of integrated functional masterbatch, 0.3-0.6 parts of ultraviolet absorber, 0.2-0.5 parts of dispersant, and 4-8 parts of hydrophobic, wear-resistant, and self-healing coating composition (based on solids).

[0007] Using the above technical solution, high-viscosity nylon 6 chips are used as the fiber-forming matrix resin to provide basic mechanical support for the industrial yarn; the integrated functional masterbatch achieves uniform dispersion and synergistic effect of multiple functional components, improving the overall performance of the industrial yarn; the ultraviolet absorber can inhibit the degradation effect of ultraviolet rays on the industrial yarn and improve the light resistance of the industrial yarn; the dispersant can promote the uniform dispersion of each raw material component during the preparation process and reduce the agglomeration of components; the hydrophobic, wear-resistant and self-healing coating composition can form a continuous and dense protective coating on the surface of the industrial yarn, improving the hydrophobicity, wear resistance and damage repair ability of the industrial yarn. The synergistic effect of each component enables the obtained industrial yarn to be suitable for the harsh service environment of marine wind power mooring cables.

[0008] Preferably, the raw materials for preparing the integrated functional masterbatch, by weight, include: 40-60 parts of ordinary nylon 6 chips, 0.05-0.15 parts of cuprous iodide, 0.2-0.5 parts of potassium bromide, 2-4 parts of N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexamethylenediamine (antioxidant 1098), 6-12 parts of nano-silicon nitride, 4-8 parts of polytetrafluoroethylene micro powder, 2-5 parts of molybdenum disulfide nanosheets, and 4-8 parts of maleic anhydride-grafted ethylene-octene copolymer.

[0009] Using the above technical solution, ordinary nylon 6 chips serve as the carrier resin for the integrated functional masterbatch, providing a uniformly dispersed carrier for the inorganic functional components. The synergistic effect of cuprous iodide, potassium bromide, and antioxidant 1098 significantly inhibits the thermo-oxidative aging and UV degradation of the fibers, improving the long-term weather resistance of the masterbatch and industrial filaments. Nano-silicon nitride enhances the wear resistance of the masterbatch and improves the mechanical load-bearing capacity of the subsequent industrial filaments. Polytetrafluoroethylene micropowder reduces the surface friction coefficient of the masterbatch and industrial filaments. Molybdenum disulfide nanosheets provide lubrication, reducing frictional damage. Maleic anhydride-grafted ethylene-octene copolymer effectively improves the interfacial bonding between the inorganic components and the organic carrier in the masterbatch, promoting uniform dispersion of each component and thus enhancing the overall performance of the subsequently prepared marine wind power cable industrial filaments.

[0010] Preferably, the preparation method of the integrated functional masterbatch is as follows: all raw materials for the preparation of the integrated functional masterbatch are added to a high-speed mixer and mixed for 5-10 minutes at 85-95℃ and 300-500 r / min. Then, the mixture is added to a twin-screw extruder and melt-blended at 230-240℃ in the feeding section, 245-255℃ in the melting section, 240-250℃ in the homogenization section, and 235-245℃ in the extrusion section, with a screw speed of 250-350 r / min. After stretching, water cooling, air drying, and pelletizing, the mixture is dried for 4-6 hours at 80-90℃ and a vacuum degree of -0.09MPa to -0.08MPa to obtain the integrated functional masterbatch.

[0011] Using the above technical solution, the set temperature and screw speed of each section of the twin-screw extruder can enable the mixture to be fully melted and blended, ensuring that the components are uniformly fused in the molten state; the subsequent stranding, water cooling, air drying and pelletizing processes can form the molten mixture into granular masterbatch; vacuum drying can remove the moisture in the masterbatch, improve the processing performance of the masterbatch, and finally obtain an integrated functional masterbatch with uniform performance and stable processing.

[0012] Preferably, the relative viscosity of the high-viscosity nylon 6 chips is 3.4-3.6; the relative viscosity of the ordinary nylon 6 chips is 2.4-2.8; the average particle size of the nano-silicon nitride is 40-70 nm; the average particle size of the polytetrafluoroethylene micro powder is 2-4 μm; and the diameter of the molybdenum disulfide nanosheets is 150-250 nm.

[0013] Using the above technical solution, the relative viscosity corresponds to a higher molecular weight, which can make the molecular chain entanglement density of high-viscosity nylon 6 chips higher, providing a solid basic mechanical skeleton for industrial filaments of cables for marine wind power generation, and improving the initial structural strength and fracture resistance of the fiber; ordinary nylon 6 chips can be used as a carrier resin or alternative material, suitable for the dispersion and fusion of integrated functional masterbatch and other components; the average particle size of nano-silicon nitride is 40-70nm, and as hard particles, it can effectively withstand frictional loads, enhancing the wear resistance and mechanical load-bearing capacity of industrial filaments; the average particle size of polytetrafluoroethylene micropowder is 2-4μm, which can reduce the surface friction coefficient of the fiber and reduce frictional damage; the diameter of molybdenum disulfide nanosheets is 150-250nm, and its layered structure slips under shear force and forms a solid lubricating film, further improving the lubrication and friction reduction effect of the fiber. The reasonable setting of each parameter allows each component to play its full role and synergistically improve the comprehensive performance of cable industrial filaments.

[0014] Preferably, the raw materials for preparing the hydrophobic, wear-resistant, and self-healing coating composition, by weight, include: 10-15 parts of fluorinated polyurethane prepolymer, 2-4 parts of epoxy resin E-51, 1-2 parts of isophorone diamine, 0.2-0.5 parts of organic bismuth catalyst, 20-30 parts of N-methylpyrrolidone, 15-25 parts of isophorone diisocyanate, 8-12 parts of hexamethylenediamine, 1-2 parts of sodium dodecylbenzenesulfonate, 2-4 parts of sodium polyacrylate, and 100-150 parts of deionized water.

[0015] Using the above technical solutions, fluorinated polyurethane prepolymers can impart excellent hydrophobicity and cross-linking curing properties to the coating; epoxy resin E-51 can enhance the structural strength and wear resistance of the coating; isophorone diamine, as a curing agent, can promote the cross-linking curing of the coating, improving its density, hardness, and wear resistance; organic bismuth catalysts can accelerate the cross-linking reaction rate of the coating components, ensuring the coating curing efficiency; N-methylpyrrolidone, as an organic solvent, can fully dissolve and mix the various coating raw materials, providing a stable system for coating film formation; isophorone diisocyanate can undergo interfacial polymerization with hexamethylenediamine to form a polyurea wall material and encapsulate the core material, thus obtaining a self-healing microadhesive. The microcapsule is composed of hexamethylenediamine as a monomer for polymerization, which synergistically forms the microcapsule wall material with isophorone diisocyanate to encapsulate and protect the core material; sodium dodecylbenzenesulfonate can improve the emulsification and dispersibility of the oil phase in the aqueous phase and promote the formation of a stable emulsion; sodium polyacrylate can act as a dispersing stabilizer to enhance the stability of the aqueous system and ensure the smooth progress of the microencapsulation reaction; deionized water serves as the aqueous phase carrier, providing a dissolution environment for each water-soluble component and a reaction medium for the interfacial polymerization reaction; the synergistic effect of the raw materials can prepare a stable hydrophobic wear-resistant self-healing coating composition for surface protection of industrial filaments used in marine wind power cables.

[0016] Preferably, the preparation method of the hydrophobic, wear-resistant, and self-healing coating composition includes the following steps:

[0017] (1) Under dry nitrogen protection, fluorinated polyurethane prepolymer, epoxy resin E-51 and organic bismuth catalyst are added to N-methylpyrrolidone, stirred and dissolved, heated to 50-60℃, and stirred at 200-300r / min for 15-20min to obtain core material solution.

[0018] (2) Dissolve sodium dodecylbenzenesulfonate and sodium polyacrylate in deionized water, and adjust the pH to 7.0-7.5 with 10% sodium hydroxide solution to obtain an aqueous solution;

[0019] (3) Mix the core material solution obtained in step (1) with isophorone diisocyanate to obtain an oil phase. Under stirring at 30-35℃ and 1400-1600r / min, slowly add the oil phase to the aqueous phase solution and emulsify for 20-30min. After emulsification, slowly add isophorone diamine and hexamethylenediamine. React under stirring at 35-40℃ for 1.5-2.5h to obtain a microcapsule suspension.

[0020] (4) Cool the microcapsule suspension obtained in step (3) to 25-30°C, add deionized water to dilute to a solid content of 20-30%, and obtain a hydrophobic wear-resistant self-healing coating composition emulsion.

[0021] Using the above technical solution, dry nitrogen protection provides a stable environment for the preparation of the core material solution, allowing the fluorinated polyurethane prepolymer, epoxy resin E-51, and organic bismuth catalyst to fully dissolve and mix evenly in N-methylpyrrolidone, forming a stable core material solution. Sodium dodecylbenzenesulfonate and sodium polyacrylate are dissolved in deionized water and the pH is adjusted to 7.0-7.5 to form a stable aqueous phase solution. The core material solution is mixed with isophorone diisocyanate to form an oil phase. After the oil phase is emulsified with the aqueous phase under specific conditions, isophorone diamine and hexamethylenediamine are added dropwise to react and form a microcapsule suspension with polyurea as the wall material and containing the core material. Cooling and diluting the microcapsule suspension to a specified solid content yields a stable hydrophobic, wear-resistant, and self-healing coating composition emulsion. This emulsion can be uniformly adhered to the surface of cable industrial yarns to form a water-repellent, wear-resistant, and self-healing film, improving the surface protection performance of the fibers.

[0022] Preferably, the ultraviolet absorber is one or more of UV-326, UV-327, and UV-329, and the dispersant is N,N'-ethylene bis-stearamide or maleic anhydride-grafted polyethylene wax.

[0023] Using the above technical solution, one or more of UV-326, UV-327, and UV-329 can be used as ultraviolet absorbers to efficiently absorb ultraviolet light and convert light energy into heat energy, inhibiting the photodegradation of nylon 6 molecular chains and ensuring the long-term weather resistance of the fiber. N,N'-ethylene bis-stearamide or maleic anhydride-grafted polyethylene wax can be used as dispersants to promote the uniform dispersion of each component in the raw material, avoid agglomeration, ensure the stability of the spinning process, and at the same time improve the interfacial bonding force between each functional component and the matrix resin, ensuring the stable performance of the fiber's mechanical properties, abrasion resistance, and seawater corrosion resistance.

[0024] This invention also provides a manufacturing process for industrial yarns used in offshore wind power cables, comprising the following steps:

[0025] S1. Dry the high-viscosity nylon 6 chips at 115-125℃ and vacuum degree of -0.09MPa to -0.06MPa for 8-12 hours to reduce the moisture content to 200-300ppm.

[0026] S2. After the high-viscosity nylon 6 chips, integrated functional masterbatch, ultraviolet absorber and dispersant obtained in step S1 are mixed evenly, they are added to a twin-screw extruder for melt blending and spinning.

[0027] S3. The molten stream extruded from the spinneret passes through a slow cooler with a height of 250-350 mm and a temperature of 245-255℃, and then enters a side-blowing window for cooling. The side-blowing air temperature is 15.5-18.5℃, the air velocity is 0.55-0.65 m / s, and the humidity is 65-75%, thus obtaining nascent fibers.

[0028] S4. Apply oil to the nascent fibers obtained in step S3 using an oiling nozzle, employing a special oiling agent for nylon 6 spinning, and control the fiber oil content to 0.6-0.8%;

[0029] S5. The oiled filament bundle from step S4 is stretched and shaped using four-stage hot rollers.

[0030] S6. After stretching and shaping in step S5, the filament bundle is subjected to hot air degreasing pretreatment at 120-150℃ for 8-12 seconds to remove free oil from the surface. Then, it is immersed in an impregnation tank containing a hydrophobic, wear-resistant, and self-healing coating composition emulsion for 8-12 seconds, followed by hot air drying at 60-80℃ for 3-5 minutes. The coating adhesion is controlled at 0.9-1.1%.

[0031] S7. After the coated filament bundle is processed by a networker, it is wound into shape at a winding speed of 2510-2530m / min and a winding tension of 130-150cN to obtain industrial filament for marine wind power generation cables.

[0032] Using the above technical solution, the high-viscosity nylon 6 chips are dried under specific temperature and vacuum conditions, which can control their moisture content within a specified range, ensuring the smooth progress of subsequent melt blending and spinning. The high-viscosity nylon 6 chips, integrated functional masterbatch, ultraviolet absorber, and dispersant are melt blended and spun using a twin-screw extruder, which can achieve uniform fusion of the components. The melt stream is cooled by a slow cooler and a side-blowing window, which can solidify the filaments to form nascent fibers with a uniform structure. The oiling treatment of the nascent fibers can improve the lubricity of the filament bundle and reduce frictional damage during subsequent processing. The fiber bundle is stretched and shaped by four stages of hot rollers to optimize the molecular chain orientation and crystallization state, thereby improving the fiber's mechanical properties. After stretching and shaped, the fiber bundle undergoes a hot air degreasing pretreatment to remove free oil from the surface. Then, it is impregnated with a hydrophobic, wear-resistant, and self-healing coating composition emulsion and dried with hot air to form a uniform protective coating on the fiber surface. The coated fiber bundle is then processed by a networker and wound under specific conditions to obtain industrial yarn for marine wind power cable with stable structure and qualified performance. This gives the fiber the mechanical, wear-resistant, weather-resistant, and water-repellent properties required for marine wind power mooring cables.

[0033] Preferably, in step S2, the temperatures of each zone in the melt blending spinning process are set as follows: Zone 1 245-255℃, Zone 2 255-265℃, Zone 3 255-265℃, Zone 4 250-260℃, Zone 5 245-255℃, and Zone 6 245-255℃; the melt enters the spinning assembly through a 15-25μm filter screen, and the temperature of the spinning box is 247-253℃.

[0034] By employing the above technical solution, the temperature limitation of each zone in melt blending spinning allows for the full melting and uniform blending of high-viscosity nylon 6 chips, integrated functional masterbatch, UV absorber, and dispersant, ensuring uniform melting and dispersion of each component. The 15-25μm filter screen can filter impurities and incompletely melted particles in the melt, preventing impurities from affecting the spinning smoothness and fiber forming quality. The spinning box temperature of 247-253℃ can maintain stable melt flowability, ensuring that the melt stream is uniform in shape when extruded from the spinneret, thus providing a guarantee for subsequent spinning forming and performance stability.

[0035] Preferably, in step S5, the process parameters for the four-stage hot roller stretching and setting are as follows:

[0036] The first pair of hot rollers has a speed of 580-590 m / min and a temperature of 55-65℃.

[0037] The second pair of hot rollers has a speed of 1855-1865 m / min and a temperature of 160-170℃.

[0038] The third pair of hot rollers has a speed of 2500-2520 m / min and a temperature of 170-180℃.

[0039] The fourth pair of hot rollers has a speed of 2450-2490 m / min and a temperature of 115-125℃.

[0040] Using the above technical solution, the speed and temperature of the first pair of hot rollers can initially stretch and preheat the filament bundle, providing a guarantee for subsequent stretching; the second and third pairs of hot rollers, through higher speeds and temperatures, promote the orientation and crystallization of nylon 6 molecular chains, improving the strength of the filament bundle; the speed and temperature settings of the fourth pair of hot rollers can achieve appropriate relaxation and shaping of the filament bundle, reduce internal stress, ensure the stability of the mechanical properties of the filament bundle, and at the same time improve the wear resistance and dimensional stability of the filament bundle, ensuring the uniformity of subsequent coating adhesion.

[0041] The beneficial effects of this invention are as follows:

[0042] High-viscosity nylon 6 chips serve as the fiber-forming matrix resin, providing fundamental mechanical support for the industrial yarn. Integrated functional masterbatch achieves uniform dispersion and synergistic effects of multiple functional components, improving the overall performance of the industrial yarn. UV absorbers inhibit the degradation of the industrial yarn by ultraviolet radiation, enhancing its lightfastness. Dispersants promote uniform dispersion of raw material components during preparation, reducing component agglomeration. A hydrophobic, abrasion-resistant, and self-healing coating composition forms a continuous and dense protective coating on the surface of the industrial yarn, improving its hydrophobicity, abrasion resistance, and damage repair capabilities. The synergistic effect of these components enables the resulting industrial yarn to withstand the harsh service environment of offshore wind power mooring cables. Detailed Implementation

[0043] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0044] The specific information on the raw materials used in the embodiments of the present invention is shown in Table 1.

[0045] Table 1

[0046] High-viscosity nylon 6 chips Relative viscosity 3.4-3.6 Ningbo Rongsu New Materials Co., Ltd. Ordinary nylon 6 chips Relative viscosity 2.4-2.8 Ningbo Rongsu New Materials Co., Ltd. Cuprous iodide Analytical Pure Shanghai Aladdin Biochemical Technology Co., Ltd. Potassium bromide Analytical Pure Shanghai Aladdin Biochemical Technology Co., Ltd. Antioxidant 1098 99% purity BASF AG Nano silicon nitride The average particle size is 40-70 nm. Hefei AVIC Nanotechnology Development Co., Ltd. polytetrafluoroethylene micro powder 99% purity, average particle size 2-4 μm Shenyang Wuliang Technology Co., Ltd. Molybdenum disulfide nanosheets The wafer diameter is 150-250nm Nanjing Xianfeng Nanomaterials Technology Co., Ltd. Maleic anhydride-grafted ethylene-octene copolymer Grafting rate: 0.8-1.0% Dow Chemicals, USA UV-326 99% purity BASF AG UV-327 99% purity BASF AG UV-329 99% purity BASF AG N,N'-Ethylenebis-stearamide 99% purity Shandong Suitai Biotechnology Co., Ltd. Maleic anhydride-grafted polyethylene wax 99% purity, average particle size 5-8μm Guangzhou Yinuo Chemical Technology Co., Ltd. Fluorinated polyurethane prepolymer NCO content 12-15% Polyurethane Industry Co., Ltd. Epoxy Resin E-51 Epoxy value 0.51~0.54 eq / 100g, purity 99.9% Guangzhou Verina Chemical Co., Ltd. Isophorone diamine 99% purity Wuhan Kanos Technology Co., Ltd. Organic bismuth catalysts BICAT 8108, bismuth content 18wt%~22wt% Leading American Chemical Company N-Methylpyrrolidone Purity ≥ 99.5%, Moisture ≤ 0.1% Shandong Jinyueyuan New Materials Co., Ltd. Isophorone diisocyanate 99% purity Wuhan Kanos Technology Co., Ltd. Hexamethylenediamine 99.9% purity Shandong Xinheng Chemical Co., Ltd. Sodium dodecylbenzenesulfonate 98% purity Wuhan Camick Technology Co., Ltd. Sodium polyacrylate 99% purity Hubei Kewode Chemical Co., Ltd. Nylon 6 spinning special oil 90% active ingredient content Hangzhou Surate Oil Products Co., Ltd.

[0047] Example 1:

[0048] This embodiment provides an industrial filament for marine wind power cable production. By weight, its preparation raw materials include: 80 parts of high-viscosity nylon 6 chips with a relative viscosity of 3.4, 6 parts of integrated functional masterbatch, 0.3 parts of ultraviolet absorber, 0.2 parts of dispersant, and 4 parts of a hydrophobic, abrasion-resistant, self-healing coating composition (based on solids). The ultraviolet absorber is UV-326, and the dispersant is N,N'-ethylene bis-stearamide.

[0049] By weight, the raw materials for preparing the integrated functional masterbatch include: 40 parts of ordinary nylon 6 chips with a relative viscosity of 2.4, 0.05 parts of cuprous iodide, 0.2 parts of potassium bromide, 2 parts of antioxidant 1098, 6 parts of nano-silicon nitride with an average particle size of 40 nm, 4 parts of polytetrafluoroethylene micro powder with an average particle size of 2 μm, 2 parts of molybdenum disulfide nanosheets with a sheet diameter of 150 nm, and 4 parts of maleic anhydride-grafted ethylene-octene copolymer.

[0050] The preparation method of integrated functional masterbatch is as follows: all raw materials for the preparation of integrated functional masterbatch are added to a high-speed mixer and mixed for 5 minutes at 85℃ and 300r / min. Then the mixture is added to a twin-screw extruder and melt-blended at 230℃ in the feeding section, 245℃ in the melting section, 240℃ in the homogenization section, and 235℃ in the extrusion section. The screw speed is 250r / min. After being stretched, water-cooled, air-dried, and pelletized, it is dried for 4 hours at 80℃ and a vacuum degree of -0.09MPa to obtain integrated functional masterbatch.

[0051] The raw materials for preparing the hydrophobic, wear-resistant, and self-healing coating composition, by weight, include: 10 parts of fluorinated polyurethane prepolymer, 2 parts of epoxy resin E-51, 1 part of isophorone diamine, 0.2 parts of organic bismuth catalyst, 20 parts of N-methylpyrrolidone, 15 parts of isophorone diisocyanate, 8 parts of hexamethylenediamine, 1 part of sodium dodecylbenzenesulfonate, 2 parts of sodium polyacrylate, and 100 parts of deionized water.

[0052] The preparation method of the hydrophobic, wear-resistant, and self-healing coating composition includes the following steps:

[0053] (1) Under dry nitrogen protection, fluorinated polyurethane prepolymer, epoxy resin E-51 and organic bismuth catalyst were added to N-methylpyrrolidone, stirred and dissolved, heated to 50°C, and stirred at 200 r / min for 15 min to obtain core material solution.

[0054] (2) Dissolve sodium dodecylbenzenesulfonate and sodium polyacrylate in deionized water, and adjust the pH to 7.0 with 10% sodium hydroxide solution to obtain an aqueous solution;

[0055] (3) Mix the core material solution obtained in step (1) with isophorone diisocyanate to obtain an oil phase. Under stirring at 30°C and 1400 r / min, slowly add the oil phase to the aqueous phase solution and emulsify for 20 min. After emulsification, slowly add isophorone diamine and hexamethylenediamine. React at 35°C for 1.5 h to obtain a microcapsule suspension.

[0056] (4) Cool the microcapsule suspension obtained in step (3) to 25°C, add deionized water to dilute to a solid content of 20%, and obtain a hydrophobic wear-resistant self-healing coating composition emulsion.

[0057] This embodiment also provides a manufacturing process for industrial yarns used in offshore wind power cables, including the following steps:

[0058] S1. Dry the high-viscosity nylon 6 chips at 115℃ and vacuum degree -0.09MPa for 8 hours to reduce the moisture content to 200ppm.

[0059] S2. After the high-viscosity nylon 6 chips, integrated functional masterbatch, ultraviolet absorber, and dispersant obtained in step S1 are mixed evenly, they are added to a twin-screw extruder for melt blending and spinning. The temperature of each zone of the screw is set as follows: zone 1 245℃, zone 2 255℃, zone 3 255℃, zone 4 250℃, zone 5 245℃, and zone 6 245℃. The melt enters the spinning assembly through a 15μm filter screen, and the temperature of the spinning box is 247℃.

[0060] S3. The molten stream extruded from the spinneret passes through a slow cooler with a height of 250 mm and a temperature of 245 °C, and then enters a side-blowing window for cooling. The side-blowing air temperature is 15.5 °C, the air velocity is 0.55 m / s, and the humidity is 65%, resulting in nascent fibers.

[0061] S4. The nascent fibers obtained in step S3 are oiled through an oil nozzle using a special oiling agent for nylon 6 spinning, and the oil content of the fibers is controlled to be 0.6%.

[0062] S5. The oiled filament bundle from step S4 is subjected to four-stage hot roller stretching and shaping, with the following process parameters:

[0063] The first pair of hot rollers has a speed of 580 m / min and a temperature of 55℃.

[0064] The second pair of hot rollers has a speed of 1855 m / min and a temperature of 160℃.

[0065] The third pair of hot rollers has a speed of 2500 m / min and a temperature of 170℃;

[0066] The fourth pair of hot rollers has a speed of 2450 m / min and a temperature of 115℃;

[0067] S6. The stretched and shaped filaments from step S5 are subjected to a hot air degreasing pretreatment at 120°C for 8 seconds to remove free oil from the surface. Then, they are immersed in an impregnation tank containing a hydrophobic, wear-resistant, and self-healing coating composition emulsion for 8 seconds, followed by hot air drying at 60°C for 3 minutes. The coating adhesion is controlled at 0.9%.

[0068] S7. After the coated filament bundle is processed by a networker, it is wound into shape at a winding speed of 2510m / min and a winding tension of 130cN to obtain industrial filament for marine wind power generation cables.

[0069] Example 2:

[0070] This embodiment provides an industrial filament for marine wind power cable production. By weight, its preparation raw materials include: 95 parts of high-viscosity nylon 6 chips with a relative viscosity of 3.6, 12 parts of integrated functional masterbatch, 0.6 parts of ultraviolet absorber, 0.5 parts of dispersant, and 8 parts of a hydrophobic, abrasion-resistant, self-healing coating composition (based on solids). The ultraviolet absorber is UV-327, and the dispersant is maleic anhydride-grafted polyethylene wax.

[0071] By weight, the raw materials for preparing the integrated functional masterbatch include: 60 parts of ordinary nylon 6 chips with a relative viscosity of 2.8, 0.15 parts of cuprous iodide, 0.5 parts of potassium bromide, 4 parts of antioxidant 1098, 12 parts of nano-silicon nitride with an average particle size of 70 nm, 8 parts of polytetrafluoroethylene micro powder with an average particle size of 4 μm, 5 parts of molybdenum disulfide nanosheets with a sheet diameter of 250 nm, and 8 parts of maleic anhydride-grafted ethylene-octene copolymer.

[0072] The preparation method of integrated functional masterbatch is as follows: all raw materials for the preparation of integrated functional masterbatch are added to a high-speed mixer and mixed for 10 minutes at 95℃ and 500r / min. Then the mixture is added to a twin-screw extruder and melt-blended at 240℃ in the feeding section, 255℃ in the melting section, 250℃ in the homogenization section, and 245℃ in the extrusion section. The screw speed is 350r / min. After being stretched, water-cooled, air-dried, and pelletized, it is dried for 6 hours at 90℃ and a vacuum degree of -0.08MPa to obtain integrated functional masterbatch.

[0073] The raw materials for preparing the hydrophobic, wear-resistant, and self-healing coating composition, by weight, include: 15 parts of fluorinated polyurethane prepolymer, 4 parts of epoxy resin E-51, 2 parts of isophorone diamine, 0.5 parts of organic bismuth catalyst, 30 parts of N-methylpyrrolidone, 25 parts of isophorone diisocyanate, 12 parts of hexamethylenediamine, 2 parts of sodium dodecylbenzenesulfonate, 4 parts of sodium polyacrylate, and 150 parts of deionized water.

[0074] The preparation method of the hydrophobic, wear-resistant, and self-healing coating composition includes the following steps:

[0075] (1) Under dry nitrogen protection, fluorinated polyurethane prepolymer, epoxy resin E-51 and organic bismuth catalyst were added to N-methylpyrrolidone, stirred and dissolved, heated to 60°C, and stirred at 300 r / min for 20 min to obtain core material solution.

[0076] (2) Dissolve sodium dodecylbenzenesulfonate and sodium polyacrylate in deionized water, and adjust the pH to 7.5 with 10% sodium hydroxide solution to obtain an aqueous solution;

[0077] (3) Mix the core material solution obtained in step (1) with isophorone diisocyanate to obtain an oil phase. Under stirring at 35°C and 1600 r / min, slowly add the oil phase to the aqueous phase solution and emulsify for 30 min. After emulsification, slowly add isophorone diamine and hexamethylenediamine. React under stirring at 40°C for 2.5 h to obtain a microcapsule suspension.

[0078] (4) Cool the microcapsule suspension obtained in step (3) to 30°C, add deionized water to dilute to a solid content of 30%, and obtain a hydrophobic wear-resistant self-healing coating composition emulsion.

[0079] This embodiment also provides a manufacturing process for industrial yarns used in offshore wind power cables, including the following steps:

[0080] S1. Dry the high-viscosity nylon 6 chips at 125℃ and vacuum degree -0.06MPa for 12h to reduce the moisture content to 300ppm;

[0081] S2. After the high-viscosity nylon 6 chips, integrated functional masterbatch, ultraviolet absorber, and dispersant obtained in step S1 are mixed evenly, they are added to a twin-screw extruder for melt blending and spinning. The temperature of each zone of the screw is set as follows: zone 1 255℃, zone 2 265℃, zone 3 265℃, zone 4 260℃, zone 5 255℃, and zone 6 255℃. The melt enters the spinning assembly through a 25μm filter screen, and the temperature of the spinning box is 253℃.

[0082] S3. The molten stream extruded from the spinneret passes through a slow cooler with a height of 350 mm and a temperature of 255 °C, and then enters a side-blowing window for cooling. The side-blowing air temperature is 18.5 °C, the air velocity is 0.65 m / s, and the humidity is 75%, thus obtaining nascent fibers.

[0083] S4. The nascent fibers obtained in step S3 are oiled through an oil nozzle using a special oiling agent for nylon 6 spinning, and the oil content of the fibers is controlled to be 0.8%.

[0084] S5. The oiled filament bundle from step S4 is subjected to four-stage hot roller stretching and shaping, with the following process parameters:

[0085] The first pair of hot rollers has a speed of 590 m / min and a temperature of 65℃.

[0086] The second pair of hot rollers has a speed of 1865 m / min and a temperature of 170℃.

[0087] The third pair of hot rollers has a speed of 2520 m / min and a temperature of 180℃.

[0088] The fourth pair of hot rollers has a speed of 2490 m / min and a temperature of 125℃;

[0089] S6. The stretched and shaped filaments from step S5 are subjected to a 12-second hot air degreasing pretreatment at 150°C to remove free oil from the surface. Then, they are immersed in an impregnation tank containing a hydrophobic, wear-resistant, and self-healing coating composition emulsion for 12 seconds, followed by hot air drying at 80°C for 5 minutes. The coating adhesion is controlled at 1.1%.

[0090] S7. After the coated filament bundle is processed by a networker, it is wound into shape at a winding speed of 2530m / min and a winding tension of 150cN to obtain industrial filament for marine wind power generation cables.

[0091] Example 3:

[0092] This embodiment provides an industrial filament for marine wind power cable production. By weight, its preparation raw materials include: 88 parts of high-viscosity nylon 6 chips with a relative viscosity of 3.5, 9 parts of integrated functional masterbatch, 0.5 parts of ultraviolet absorber, 0.4 parts of dispersant, and 6 parts of a hydrophobic, abrasion-resistant, self-healing coating composition (based on solids). The ultraviolet absorber is UV-329, and the dispersant is N,N'-ethylene bis-stearamide.

[0093] By weight, the raw materials for preparing the integrated functional masterbatch include: 50 parts of ordinary nylon 6 chips with a relative viscosity of 2.6, 0.1 parts of cuprous iodide, 0.35 parts of potassium bromide, 3 parts of antioxidant 1098, 9 parts of nano-silicon nitride with an average particle size of 55 nm, 6 parts of polytetrafluoroethylene micro powder with an average particle size of 3 μm, 3.5 parts of molybdenum disulfide nanosheets with a sheet diameter of 200 nm, and 6 parts of maleic anhydride-grafted ethylene-octene copolymer.

[0094] The preparation method of integrated functional masterbatch is as follows: all raw materials for the preparation of integrated functional masterbatch are added to a high-speed mixer and mixed for 7 minutes at 90℃ and 400r / min. Then the mixture is added to a twin-screw extruder and melt-blended at 235℃ in the feeding section, 250℃ in the melting section, 245℃ in the homogenization section, and 240℃ in the extrusion section. The screw speed is 300r / min. After being stretched, water-cooled, air-dried, and pelletized, it is dried for 5 hours at 85℃ and a vacuum degree of -0.085MPa to obtain integrated functional masterbatch.

[0095] The raw materials for preparing the hydrophobic, wear-resistant, and self-healing coating composition, by weight, include: 12 parts of fluorinated polyurethane prepolymer, 3 parts of epoxy resin E-51, 1.5 parts of isophorone diamine, 0.35 parts of organic bismuth catalyst, 25 parts of N-methylpyrrolidone, 20 parts of isophorone diisocyanate, 10 parts of hexamethylenediamine, 1.5 parts of sodium dodecylbenzenesulfonate, 3 parts of sodium polyacrylate, and 125 parts of deionized water.

[0096] The preparation method of the hydrophobic, wear-resistant, and self-healing coating composition includes the following steps:

[0097] (1) Under dry nitrogen protection, fluorinated polyurethane prepolymer, epoxy resin E-51 and organic bismuth catalyst were added to N-methylpyrrolidone, stirred and dissolved, heated to 55°C, and stirred at 250 r / min for 17 min to obtain core material solution.

[0098] (2) Dissolve sodium dodecylbenzenesulfonate and sodium polyacrylate in deionized water, and adjust the pH to 7.2 with 10% sodium hydroxide solution to obtain an aqueous solution;

[0099] (3) Mix the core material solution obtained in step (1) with isophorone diisocyanate to obtain an oil phase. Under stirring at 32°C and 1500 r / min, slowly add the oil phase to the aqueous phase solution and emulsify for 25 min. After emulsification, slowly add isophorone diamine and hexamethylenediamine. React at 38°C for 2 h to obtain a microcapsule suspension.

[0100] (4) Cool the microcapsule suspension obtained in step (3) to 28°C, add deionized water to dilute to a solid content of 25%, and obtain a hydrophobic wear-resistant self-healing coating composition emulsion.

[0101] This embodiment also provides a manufacturing process for industrial yarns used in offshore wind power cables, including the following steps:

[0102] S1. Dry the high-viscosity nylon 6 chips at 120℃ and vacuum degree -0.075MPa for 10h to reduce the moisture content to 250ppm.

[0103] S2. After the high-viscosity nylon 6 chips, integrated functional masterbatch, ultraviolet absorber, and dispersant obtained in step S1 are mixed evenly, they are added to a twin-screw extruder for melt blending and spinning. The temperature of each zone of the screw is set as follows: zone 1 250℃, zone 2 260℃, zone 3 260℃, zone 4 255℃, zone 5 250℃, and zone 6 250℃. The melt enters the spinning assembly through a 20μm filter screen, and the temperature of the spinning box is 250℃.

[0104] S3. The molten stream extruded from the spinneret passes through a slow cooler with a height of 300 mm and a temperature of 250 °C, and then enters a side-blowing window for cooling. The side-blowing air temperature is 17 °C, the air velocity is 0.6 m / s, and the humidity is 70%, thus obtaining nascent fibers.

[0105] S4. The nascent fibers obtained in step S3 are oiled through an oil nozzle using a special oiling agent for nylon 6 spinning, and the oil content of the fibers is controlled to be 0.7%.

[0106] S5. The oiled filament bundle from step S4 is subjected to four-stage hot roller stretching and shaping, with the following process parameters:

[0107] The first pair of hot rollers has a speed of 585 m / min and a temperature of 60℃.

[0108] The second pair of hot rollers has a speed of 1860 m / min and a temperature of 165℃.

[0109] The third pair of hot rollers has a speed of 2510 m / min and a temperature of 175℃.

[0110] The fourth pair of hot rollers has a speed of 2470 m / min and a temperature of 120℃;

[0111] S6. The stretched and shaped filament bundle from step S5 is subjected to a 10-second hot air degreasing pretreatment at 135°C to remove free oil from the surface. Then, it is immersed in an impregnation tank containing a hydrophobic, wear-resistant, and self-healing coating composition emulsion for 10 seconds, followed by hot air drying at 70°C for 4 minutes. The coating adhesion is controlled at 1.0%.

[0112] S7. After the coated filament bundle is processed by a networker, it is wound into shape at a winding speed of 2520m / min and a winding tension of 140cN to obtain industrial filament for marine wind power generation cables.

[0113] Comparative Example 1:

[0114] An industrial yarn for marine wind power cable and its production process, which differs from Example 3 only in that: no integrated functional masterbatch is added, and an equal amount of ordinary nylon 6 chips are used instead.

[0115] Comparative Example 2:

[0116] An industrial yarn for marine wind power cable and its production process, which differs from Example 3 only in that: cuprous iodide, potassium bromide and antioxidant 1098 are not added to the integrated masterbatch, and are replaced with an equal amount of nylon 6 chips.

[0117] Comparative Example 3:

[0118] An industrial filament for marine wind power cable production and its manufacturing process are disclosed. The only difference between this and Example 3 is that nano-silicon nitride is not added to the integrated masterbatch, and an equal amount of nylon 6 chips are used instead.

[0119] Comparative Example 4:

[0120] An industrial filament for marine wind power generation cables and its production process are disclosed. The only difference between this and Example 3 is that polytetrafluoroethylene micro powder and molybdenum disulfide nanosheets are not added to the integrated masterbatch, but are replaced with an equal amount of nylon 6 chips.

[0121] Comparative Example 5:

[0122] An industrial filament for marine wind power cable and its production process, differing from Example 3 only in that the hydrophobic, wear-resistant, and self-healing coating composition is replaced with perfluorohexyl ethyl acrylate (purchased from Wuhan Kanos Technology Co., Ltd., purity 99%) with equal solids content.

[0123] Comparative Example 6:

[0124] An industrial filament for offshore wind power generation cables and its production process differ from Example 3 only in that: in the S3 cooling process, the side-blowing wind speed is increased to 1.0 m / s and the temperature is increased to 30°C.

[0125] Comparative Example 7:

[0126] An industrial yarn for marine wind power cable and its production process are disclosed. The only difference between this yarn and Example 3 is that maleic anhydride-grafted ethylene-octene copolymer is not added to the integrated masterbatch, but is replaced with an equal amount of nylon 6 chips.

[0127] Comparative Example 8:

[0128] An industrial yarn for marine wind power cable production and its manufacturing process are disclosed, which differ from Example 3 only in that ordinary nylon 6 chips are used instead of high-viscosity nylon 6 chips.

[0129] The cable industrial yarns obtained in Examples 1-3 and Comparative Examples 1-8 were tested for breaking strength, breaking elongation, abrasion resistance, heat aging strength retention, seawater corrosion resistance, and surface water repellency. The testing methods and standards for each property are as follows:

[0130] (a) Fracture strength and elongation at break

[0131] The test was conducted according to GB / T 14344-2008, "Test Method for Tensile Properties of Chemical Fiber Filaments". The clamping distance was 500 mm, and the tensile speed was 500 mm / min. Ten valid specimens were tested for each sample, and the arithmetic mean was taken. The formula for calculating the breaking strength is:

[0132] Fracture strength (cN / dtex) = Fracture force (cN) / Linear density (dtex).

[0133] (ii) Wear resistance

[0134] The test was conducted according to the "FZ / T 01058-1999 Test Method for Abrasion Resistance of Textile Fibers - Reciprocating Abrasion Tester Method". A 35g weight was used, 400-grit wet sandpaper was used as the friction material, and the reciprocating speed was 75 cycles / min. The number of reciprocating cycles (in ten thousand cycles) at which fiber breakage occurred was recorded. Ten valid samples were tested for each sample, and the arithmetic mean was taken.

[0135] (III) Strength retention rate during thermal aging

[0136] The fiber sample was placed in a constant temperature oven at 180℃ for 4 hours of heat aging. After removal, it was equilibrated for 24 hours under standard atmospheric conditions (temperature 20±2℃, relative humidity 65±5%). The breaking strength after aging was tested according to GB / T 14344-2008, and the strength retention rate was calculated.

[0137] Strength retention rate (%) = (fracture strength after aging / initial fracture strength) × 100%.

[0138] (iv) Resistance to seawater corrosion

[0139] The fiber samples were immersed in 5% sodium chloride (NaCl) simulated seawater at 25±2℃ for 168 hours (7 days). After removal, they were rinsed with deionized water and dried to constant weight in a vacuum drying oven at 60℃. The breaking strength after immersion was tested according to GB / T 14344-2008, and the strength retention rate was calculated.

[0140] Strength retention rate (%) = (breaking strength after immersion / initial breaking strength) × 100%.

[0141] (v) Surface water repellency

[0142] Using a contact angle meter, 2 μL of deionized water was dropped onto the fiber surface, and the static contact angle was measured. Five different locations were measured for each sample, and the arithmetic mean was taken.

[0143] The results are shown in Tables 2 and 3.

[0144] Table 2 Mechanical and Abrasion Resistance Properties

[0145]

[0146] Table 3 Weather resistance, corrosion resistance and water repellency

[0147]

[0148] Using Example 3 as the control group, the performance differences and causes of Comparative Examples 1-8 are analyzed as follows:

[0149] Comparative Example 1: Without the addition of integrated functional masterbatch, an equal amount of ordinary nylon 6 chips were used as a substitute. The breaking strength decreased from 8.62 cN / dtex to 7.50 cN / dtex (a decrease of 12.99%), the abrasion resistance decreased from 72,000 cycles to 44,000 cycles (a decrease of 38.9%), the heat aging strength retention rate decreased from 92.5% to 85.2% (a decrease of 7.9%), the seawater resistance strength retention rate decreased from 92.8% to 84.1% (a decrease of 9.4%), and the surface contact angle decreased from 133° to 118°. Integrated functional masterbatch uses pre-dispersion technology to uniformly disperse anti-aging, wear-resistant, lubricating, and compatibilizing components at the nanoscale in the matrix. However, the lack of nano-silicon nitride hard reinforcing phase and solid lubricating components leads to a decrease in load-bearing capacity and a shortened wear life. It not only loses the synergistic reinforcement mechanism of "hard points-soft lubrication" but also the synergistic effect of the cuprous iodide-potassium bromide thermo-oxidative stabilization system and hindered phenolic antioxidant, resulting in a comprehensive deterioration of mechanical properties, wear resistance, and weather resistance. Simultaneously, the absence of masterbatch leads to a lack of lubricating migration components in the fiber body, significantly reducing surface wear resistance.

[0150] Comparative Example 2: The integrated masterbatch did not contain cuprous iodide, potassium bromide, or antioxidant 1098. The heat aging strength retention rate decreased from 92.5% to 68.5% (a decrease of 25.9%), and the seawater resistance strength retention rate decreased from 92.8% to 71.8% (a decrease of 22.6%). Cuprous iodide and potassium bromide, as highly efficient thermo-oxidative-UV composite stabilizers, synergistically work with antioxidant 1098 (a hindered phenolic main antioxidant) to capture macromolecular free radicals and inhibit the thermo-oxidative and photo-oxidative degradation of nylon 6 molecular chains, forming a complete aging-resistant protective system. Without this system, the PA6 molecular chains underwent severe degradation under thermo-oxidative and seawater erosion, leading to a sharp decline in long-term weather resistance. It is noteworthy that the initial breaking strength of this comparative example (8.50 cN / dtex) is only slightly different from that of Example 3, demonstrating that the antioxidant system primarily affects long-term aging performance rather than initial mechanical properties.

[0151] Comparative Example 3: No nano-silicon nitride was added to the integrated masterbatch. The tensile strength decreased from 8.62 cN / dtex to 8.05 cN / dtex (a decrease of 6.6%), and the wear resistance decreased from 72,000 cycles to 41,000 cycles (a decrease of 43.06%). Nano-silicon nitride, as the hard skeleton component in the "multi-level wear-resistant system," bears the main load and protects the matrix during friction. Its absence means the fibers lose the support of the hard reinforcing phase, making the surface more prone to plastic deformation and wear under frictional stress, resulting in a significant reduction in load-bearing capacity and wear life.

[0152] Comparative Example 4: The integrated masterbatch lacked polytetrafluoroethylene (PTFE) micropowder and molybdenum disulfide (MoD) nanosheets. Wear resistance decreased from 72,000 cycles to 45,000 cycles (a decrease of 34.72%). PTFE micropowder provides an extremely low surface friction coefficient, and MoD nanosheets undergo interlaminar slippage under shear force to form a transferred lubricating film; the two work synergistically to construct a solid lubricating layer. The absence of these lubricating components increased the fiber surface friction coefficient, intensified frictional heat accumulation, leading to a faster wear rate and a significant decrease in wear resistance.

[0153] Comparative Example 5: The hydrophobic, abrasion-resistant, and self-healing coating composition was replaced with a conventional fluorinated acrylate water-repellent finishing agent (without microcapsule self-healing function). Abrasion resistance decreased from 72,000 cycles to 41,000 cycles (a decrease of 43.06%), seawater resistance retention decreased from 92.8% to 82.8% (a decrease of 10.8%), and the surface contact angle decreased to 125°. Although conventional perfluoroalkyl acrylate water-repellent agents can provide a certain water-repellent effect, they do not possess a microcapsule self-healing structure. After the coating is damaged during friction, it cannot repair itself, resulting in a significant decrease in abrasion resistance, mainly due to the coating's weak abrasion resistance and significantly reduced seawater resistance.

[0154] Comparative Example 6: The side-blowing wind speed was increased to 1.0 m / s, and the temperature was increased to 30℃. The breaking strength decreased from 8.62 cN / dtex to 7.85 cN / dtex (a decrease of 8.9%), the abrasion resistance decreased to 52,000 cycles (a decrease of 27.8%), and the seawater resistance strength retention rate decreased to 88.2% (a decrease of 5.0%). The excessively high wind speed and temperature caused the melt stream to cool too quickly and unevenly, generating internal stress within the fiber and potentially leading to differences in the core-sheath structure. This resulted in decreased molecular chain regularity, increased defects, and simultaneous deterioration of mechanical properties, abrasion resistance, and seawater resistance.

[0155] Comparative Example 7: The integrated masterbatch without maleic anhydride-grafted ethylene-octene copolymer. The tensile strength decreased from 8.62 cN / dtex to 7.92 cN / dtex (a decrease of 8.1%), and the abrasion resistance decreased to 40,000 cycles (a decrease of 44.4%). Maleic anhydride-grafted ethylene-octene copolymer acts as a reactive compatibilizer; its maleic anhydride groups react with the terminal amino groups of PA6 and simultaneously form hydrogen bonds with the hydroxyl groups on the surface of nanoparticles, improving the interfacial bonding between the inorganic filler and the organic matrix. Without this component, the interfacial bonding between the nano-silicon nitride, molybdenum disulfide, and other inorganic particles and the PA6 matrix is ​​weak, making them prone to interfacial debonding and particle shedding under stress, leading to reduced stress transfer efficiency and a significant decrease in fiber strength and abrasion resistance.

[0156] Comparative Example 8: Replacing high-viscosity nylon 6 chips with ordinary nylon 6 chips resulted in a decrease in breaking strength from 8.62 cN / dtex to 7.68 cN / dtex (a decrease of 10.9%), a decrease in heat aging strength retention from 92.5% to 86.5% (a decrease of 6.5%), and a decrease in seawater resistance strength retention from 85.6% (a decrease of 7.8%). Ordinary nylon 6 chips have a relative viscosity of 2.4–2.8 and a significantly lower molecular weight than high-viscosity nylon 6 chips, resulting in lower molecular chain entanglement density and poorer initial mechanical properties and environmental corrosion resistance. Conventional viscosity chips have lower molecular weights and shorter molecular chains, leading to insufficient initial mechanical properties. Furthermore, the molecular chains are more prone to breakage under harsh environments, resulting in a comprehensive decline in strength, weather resistance, and seawater resistance.

[0157] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. An industrial filament for marine wind power generation cables, characterized in that, The raw materials for its preparation, by weight, include: 80-95 parts of high-viscosity nylon 6 chips; 6-12 parts of integrated functional masterbatch; 0.3-0.6 parts of ultraviolet absorber; Dispersant 0.2-0.5 parts; 4-8 parts of a hydrophobic, abrasion-resistant, self-healing coating composition (based on solids).

2. The industrial wire for marine wind power generation cables according to claim 1, characterized in that, By weight, the raw materials for preparing the integrated functional masterbatch include: 40-60 parts of ordinary nylon 6 chips, 0.05-0.15 parts of cuprous iodide, 0.2-0.5 parts of potassium bromide, 2-4 parts of N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexamethylenediamine, 6-12 parts of nano-silicon nitride, 4-8 parts of polytetrafluoroethylene micro powder, 2-5 parts of molybdenum disulfide nanosheets, and 4-8 parts of maleic anhydride-grafted ethylene-octene copolymer.

3. The industrial wire for marine wind power generation cables according to claim 2, characterized in that, The preparation method of the integrated functional masterbatch is as follows: all raw materials for the preparation of the integrated functional masterbatch are added to a high-speed mixer and mixed for 5-10 minutes at 85-95℃ and 300-500 r / min. Then, the mixture is added to a twin-screw extruder and melt-blended at 230-240℃ in the feeding section, 245-255℃ in the melting section, 240-250℃ in the homogenization section, and 235-245℃ in the extrusion section, with a screw speed of 250-350 r / min. After stretching, water cooling, air drying, and pelletizing, the mixture is dried for 4-6 hours at 80-90℃ and a vacuum degree of -0.09MPa to -0.08MPa to obtain the integrated functional masterbatch.

4. The industrial wire for marine wind power generation cables according to claim 2, characterized in that, The relative viscosity of the high-viscosity nylon 6 chips is 3.4-3.6; the relative viscosity of the ordinary nylon 6 chips is 2.4-2.8; the average particle size of the nano-silicon nitride is 40-70 nm; the average particle size of the polytetrafluoroethylene micro powder is 2-4 μm; and the diameter of the molybdenum disulfide nanosheets is 150-250 nm.

5. The industrial wire for marine wind power generation cables according to claim 1, characterized in that, The raw materials for preparing the hydrophobic, wear-resistant, and self-healing coating composition, by weight, include: 10-15 parts of fluorinated polyurethane prepolymer, 2-4 parts of epoxy resin E-512, 1-2 parts of isophorone diamine, 0.2-0.5 parts of organic bismuth catalyst, 20-30 parts of N-methylpyrrolidone, 15-25 parts of isophorone diisocyanate, 8-12 parts of hexamethylenediamine, 1-2 parts of sodium dodecylbenzenesulfonate, 2-4 parts of sodium polyacrylate, and 100-150 parts of deionized water.

6. The industrial wire for marine wind power generation cables according to claim 5, characterized in that, The preparation method of the hydrophobic, wear-resistant, and self-healing coating composition includes the following steps: (1) Under dry nitrogen protection, fluorinated polyurethane prepolymer, epoxy resin E-51 and organic bismuth catalyst are added to N-methylpyrrolidone, stirred and dissolved, heated to 50-60℃, and stirred at 200-300r / min for 15-20min to obtain core material solution. (2) Dissolve sodium dodecylbenzenesulfonate and sodium polyacrylate in deionized water, adjust the pH to 7.0-7.5, and obtain an aqueous solution; (3) Mix the core material solution obtained in step (1) with isophorone diisocyanate to obtain an oil phase. Under stirring at 30-35℃ and 1400-1600r / min, slowly add the oil phase to the aqueous phase solution and emulsify for 20-30min. After emulsification, slowly add isophorone diamine and hexamethylenediamine. React under stirring at 35-40℃ for 1.5-2.5h to obtain a microcapsule suspension. (4) Cool the microcapsule suspension obtained in step (3) to 25-30°C, add deionized water to dilute to a solid content of 20-30%, and obtain a hydrophobic wear-resistant self-healing coating composition emulsion.

7. The industrial wire for marine wind power generation cables according to claim 1, characterized in that, The ultraviolet absorber is one or more of UV-326, UV-327, and UV-329, and the dispersant is N,N'-ethylene bis-stearamide or maleic anhydride-grafted polyethylene wax.

8. A production process for industrial yarn for marine wind power generation cables according to any one of claims 1-7, characterized in that, Includes the following steps: S1. Dry the high-viscosity nylon 6 chips at 115-125℃ and vacuum degree of -0.09MPa to -0.06MPa for 8-12 hours to reduce the moisture content to 200-300ppm. S2. After the high-viscosity nylon 6 chips, integrated functional masterbatch, ultraviolet absorber and dispersant obtained in step S1 are mixed evenly, they are added to a twin-screw extruder for melt blending and spinning. S3. The molten stream extruded from the spinneret passes through a slow cooler with a height of 250-350 mm and a temperature of 245-255℃, and then enters a side-blowing window for cooling. The side-blowing air temperature is 15.5-18.5℃, the air velocity is 0.55-0.65 m / s, and the humidity is 65-75%, thus obtaining nascent fibers. S4. Apply oil to the nascent fibers obtained in step S3 using an oiling nozzle, employing a special oiling agent for nylon 6 spinning, and control the fiber oil content to 0.6-0.8%; S5. The oiled filament bundle from step S4 is stretched and shaped using four-stage hot rollers. S6. After stretching and shaping in step S5, the filament bundle is pretreated with hot air degreasing, then immersed in an impregnation tank containing a hydrophobic, wear-resistant, and self-healing coating composition emulsion for 8-12 seconds, followed by hot air drying at 60-80℃ for 3-5 minutes. The coating adhesion is controlled at 0.9-1.1%. S7. After the coated filament bundle is processed by a networker, it is wound into shape at a winding speed of 2510-2530m / min and a winding tension of 130-150cN to obtain industrial filament for marine wind power generation cables.

9. The production process of industrial yarn for marine wind power generation cables according to claim 8, characterized in that, In step S2, the temperatures of each zone in the melt blending spinning are set as follows: Zone 1 245-255℃, Zone 2 255-265℃, Zone 3 255-265℃, Zone 4 250-260℃, Zone 5 245-255℃, and Zone 6 245-255℃; the melt enters the spinning assembly through a 15-25μm filter screen, and the temperature of the spinning box is 247-253℃.

10. The production process of industrial yarn for marine wind power generation cables according to claim 8, characterized in that, In step S5, the process parameters for the four-stage hot roller stretching and setting are as follows: The first pair of hot rollers has a speed of 580-590 m / min and a temperature of 55-65℃. The second pair of hot rollers has a speed of 1855-1865 m / min and a temperature of 160-170℃. The third pair of hot rollers has a speed of 2500-2520 m / min and a temperature of 170-180℃. The fourth pair of hot rollers has a speed of 2450-2490 m / min and a temperature of 115-125℃.